The Terror of History: Solar Eclipses and the Origins of Social Complexity and Complex Thinking - Eric Roca Fernandez; Anastasia Litina (ZBW - Leibniz Information Centre for Economics, 2020)
Our research advances the hypothesis and empirically establishes that a higher incidence of solar eclipses is associated with higher social complexity and complex thinking in premodern societies. We construct a novel dataset of solar eclipses' incidence at the ethnic-group level, bringing together a wide range of historical, ethnic and GIS data sources. We exploit variations in the exposure to solar eclipses in a set of 1267 ethnic groups derived from Murdock's 1967 Ethnographic Atlas. Variation in the exposure to total eclipses is exogenous, as eclipses are randomly and sparsely distributed all over the globe. Moreover, unlike other natural phenomena, solar eclipses do not destroy capital |be it human or physical. We use jurisdictional hierarchy levels, political integration and class stratification to account for social complexity. Increasing levels of gods' involvement in human affairs and the play of games proxy for complex thinking. Our results are robust to a wide range of geographical and ethnic-group controls as well as to a horse race regression between solar eclipses and other natural phenomena: lunar eclipses, earthquakes and volcano eruptions. As a potential mechanism, we hypothesize that solar eclipses and the fear they instilled raise the demand for explanations. Societies that experience frequently such episodes develop more complex societal structures and become more versed in complex thinking in an attempt to comprehend and eventually control the natural environment.
Keywords: O1; Z12; P16; 330